Grade 8 students' academic achievement in World History using jigsaw - Mandin, Steven Rigor; Martin, Aiza B.; Abatol, Saudia Arabiya Mae C.; Bansale, Jay C. (CV. Yudhistt Fateeh, 2025)
This study assessed the academic achievement of twenty-five Grade 8 Diligence students at Banahao National High School in World History using the jigsaw method. Employing a mixed-method design, the study utilized pre-and post-assessments to evaluate students' academic performance before and after implementing the jigsaw. The Wilcoxon signed-rank test was applied to determine the significant differences in scores between the pre- and post-assessments. Results showed an increase in median values from 16 in the pre-assessment to 28 in the post-assessment. The results indicate the effectiveness of the intervention in improving the academic performance of the students. Also, the p-value is less than 0.05, showing that there is a significant difference in the class performance. A thematic analysis was also used to examine students' experiences with the jigsaw. Students' responses from the FGD show that the jigsaw has enhanced students' class performance. It encourages cooperation and participation, builds and develops students' interaction, and promotes fun and practical learning. Both findings indicated improved academic achievement, with most students attaining satisfactory scores in the post-assessment. Additionally, there was notable active participation during class discussions and positive feedback from students regarding their learning experience with the method.